Koncept plemenitog divljaka u Kostnerovom vesternu Ples sa vukovima (Philologia, 2021)
This paper analyzes Costner’s Dances with Wolves, and does so through the lens of Rousseau’s concept of the noble savage. The paper’s main idea is that Costner’s Sioux, as being ethically superior to his white Euro-Americans (in terms of their treatment of nature and also in terms of their approach to inter-human relations), are the film’s realization of the philosophical concept of the noble savage. This film defies the popular westerns starring John Wayne, where the Native Americans are always depicted negatively, so with its Rousseauian political philosophy it transvalues the Hobbesian view of the Native Americans, as being predominant in Europe and North America ever since the 17th century. By siding with Rousseau’s philosophy, Dances with Wolves undermines eurocentrism as the idea that European-type societies are superior to the Native American social system.
Keywords: Costner; Rousseau; noble savage; Native Americans; ethics